The Characterization of Oyster Shell (Crassostrea gigas) as Adsorbent in The Removal of Cr(VI) Ions. A Study of NaOH and H2SO4 Activation Effect - Lia Handayani; Cut Rahmawati; Nurhayati Nurhayati; Yayuk Astuti; Adi Darmawan (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : Oyster shell as one of the highest bio-waste in Alue Naga Aceh Besar District, Indonesia, was used as an adsorbent to remove a heavy metal Cr (VI) ion. The study was started by calcinating oyster shells at a high temperature of 800 ºC for 3 hours. The effect of various acid (H2SO4) and base (NaOH) activator was studied using characterization and adsorption experiments. The characterization obtained the sample activated by 10% NaOH (Na10-ACT) and 10% H2SO4 (H10-ACT) had the highest surface area which had 14.23 m2/g, 10.77 m2/g, respectively. Furthermore, the adsorption experiments confirmed the highest surface area by showing the highest Cr (IV) ion removal of 57.66%, 70.7%, respectively. The further investigation using X-ray fluorescence (XRF) determined that the Na10-ACT adsorbent has a better composition compared to the H10-ACT due to its high purities.Abstrak : Cangkang tiram sebagai salah satu bio-limbah padat di Desa Alue Naga Kabupaten Aceh Besar, digunakan sebagai adsorben untuk menghilangkan ion logam berat Cr (IV). Penelitian ini diawali dengan mengkalsinasi cangkang tiram pada temperatur tinggi 800ºC selama tiga jam. Pengaruh penambahan aktivator asam (H2SO4) dan basa (NaOH) juga dipelajari melalui karakterisasi dan pengujian adsorpsi. Hasil karakterisasi menunjukkan sampel yang diaktivasi dengan 10% NaOH (Na10-ACT) dan 10% H2SO4 (H10-ACT) memiliki luas permukaan tertinggi yaitu 14,23 m2/g, 10,77 m2/g, masing-masing. Lebih lanjut, pengujian adsorpsi juga mendukung luas permukaan yang tinggi dengan menghilangkan ion Cr (IV) sebesar 57,66%, 70,7%, masing-masing. Investigasi melalui analisa XRF menyimpulkan bahwa Na10-ACT memiliki komposisi yang lebih baik dibanding H10-ACT karena memiliki kemurnian yang tinggi.